Regeneration of Nothofagus dombeyi (Mirb.) Ørst. in little to moderately disturbed southern beech forests in the Andes of Patagonia (Argentina) - Zerbe, Stefan (2023)
Natural forests and stands subjected to little to moderate human impact are continuously declining worldwide and with these, their biodiversity and ecosystem services. Many Nothofagus forests in the south of the South American continent are in a pristine state or only moderately impacted by humans. Forest grazing by livestock, in the past and still today often practiced in a non-sustainable way is, however, increasingly under discussion to meet current environmental and socio-economic challenges. Accordingly, we investigate the regeneration of Nothofagus dombeyi, a keystone species of the Patagonian Andes, in secondary forests in Argentinian northern Patagonia, particularly addressing the role of disturbance through grazing by livestock at various intensities. We test the hypothesis that the regeneration of this tree species is favored by grazing impact and, thus, disturbance of the herb layer and soil surface. In support of our hypothesis, Nothofagus dombeyi regeneration was significantly higher in terms of individuals and height classes in moderately grazed forests. Multivariate analysis shows significant positive effects of moderate grazing pressure, herb layer cover, and the occurrence of bare soil on the regeneration of Nothofagus dombeyi. Our results show that an integration of livestock grazing and forest regeneration is possible and that agroforestry systems can be an adequate management option for stakeholders in the region. A grazing management can also be part of a forest fire prevention strategy. However, the regeneration success and grazing pressure should be continuously monitored.